51.0k views
2 votes
X(x+3)-x
I keep getting x+3 but that’s not an option

User AndrewJE
by
5.4k points

2 Answers

6 votes
This is answer:
x(x+3)-x
or
1x(1x+3)-1x
1x+3x+-1x
=3x
First you multiply and then u would add the like terms.
User Sudheej
by
6.3k points
4 votes

Hey there!

Answer =
x^(2)+2x

Step-by-step explanation:

Let's simplify step-by-step.

x(x + 3) -x

Distribute:

= (x)(x) + (x)(3) + -x

=
x^(2)+3x+-x

Combine Like Terms:

=
x^(2)+3x+-x

=
(x^(2))+(3x+-x)

=
x^(2)+2x

So therefore, that is how you found your answer:
x^(2)+2x

User Orimdominic
by
5.2k points